Association of Daily Activity Regularity With Functional Recovery in Patients With Stroke and Spinal Cord Injury: A Prospective Actigraphy Study - Yu-Hsuan Lin; Chen Lin; Chueh-Hung Wu; Hsiang-Chih Chang; Huey-Wen Liang; Shao-Yu Chen; Kuan-Lin Sung; Wei-Chen Hsu (Annals of Rehabilitation Medicine, 2026)
Objective: To determine whether the stability of daily physical activity, quantified by interdaily stability (IS), is associated with activities of daily living (ADL) recovery during inpatient neurorehabilitation, independent of overall activity level, we examined the association between physical activity stability and ADL recovery.Methods: This prospective study recruited 161 patients with stroke or spinal cord injury (mean age: 62.4±14.8 years; 42% female) from two hospitals. Physical activity was assessed using actigraphy for seven days after admission. IS represented activity regularity, and M10 the total activity volume during the most active 10-hour period. ADL was evaluated using the Barthel Index (BI) (baseline BI=32.5±22.9; discharge BI=61.1±28.6). Multiple linear regression analyses examined IS, M10, and ADL recovery, adjusting for baseline BI, age, sex, hospital stay, days from onset to rehabilitation admission, and diagnosis group.Results: Higher IS during the first week after admission was significantly associated with better ADL recovery at discharge after controlling for all covariates (B=30.86, p=0.005). In contrast, total physical activity (M10) was not significantly associated with ADL recovery (B=-0.11, p=0.313). Younger age, lower baseline BI, longer length of stay, and shorter onset-to-admission time were also associated with greater ADL recovery.Conclusion: Greater activity stability was associated with greater ADL improvement in patients with stroke, but not in those with spinal cord injury. IS may be a clinically relevant behavioral marker during inpatient rehabilitation, although its causal role remains to be established.